Discover the answers to your questions at Westonci.ca, where experts share their knowledge and insights with you. Get quick and reliable solutions to your questions from a community of seasoned experts on our user-friendly platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.

PLEASE HELP I WILL GIVE BRAINLIEST TO BEST ANSWER WITH STEP BY STEP DIRECTIONS!!!!

For v = -3(r - 3) when r = -1 , what does v equal?


Sagot :

V=12
Equation: v=-3(-1-3)


V=-3(-4)
V=12

v = 3 (r - 1)

v = 3(- 1 - 3) ---- substititing

v = -3 - 9 ----- solved the parenthesis

v = -12 ----- -3 -9 = -12